Phosphorus fractions in sandy soils of vineyards in Southern Brazil Frações de fósforo em solos arenosos cultivados com videira na região sul do Brasil - Schmitt D.E.* (2013)
Phosphorus (P) applications to vineyards can cause P accumulation in the soil and maximize pollution risks. This study was carried out to quantify the accumulation of P fractions in sandy soils of vineyards in southern Brazil. Soil samples (layers 0-5, 6-10 and 11-20 cm) were collected from a native grassland area and two vineyards, after 14 years (vineyard 1) and 30 years (vineyard 2) of cultivation, in Santana do Livramento, southern Brazil, and subjected to chemical fractionation of P. Phosphorus application, especially to the 30-year-old vineyard 2, increased the inorganic P content down to a depth of 20 cm, mainly in the labile fractions extracted by anion-exchange resin and NaHCO3, in the moderately labile fraction extracted by 0.1 and 0.5 mol L-1 NaOH, and in the non-labile fraction extracted by 1 mol L-1 HCl, indicating the possibility of water eutrophication. Phosphorus application and grapevine cultivation time increased the P content in the organic fraction extracted by NaHCO3 from the 0-5 cm layer, and especially in the moderately labile fraction extracted by 0.1 mol L-1 NaOH, down to a depth of 20 cm.